18F-fluorodeoxyglucose positron emission tomography is useful for the diagnosis of intraocular sarcoidosis in patients with a normal CT scan. Issue 11 (18th January 2019) - Chauvelot, Pierre; Skanjeti, Andrea; Jamilloux, Yvan; de Parisot, Audrey; Broussolle, Christiane; Denis, Philippe; Ramackers, Jean Marie; Giammarile, Francesco; Kodjikian, Laurent; Seve, Pascal
Abstract : Aim: To assess the usefulness of 18 F-fluorodeoxyglucose positron emission tomography ( 18 F-FDG PET/CT) and the predictive factors for the diagnosis of sarcoidosis in patients with uveitis who have normal thoracic tomography. Methods: We retrospectively reviewed 67 consecutive patients with uveitis of unknown aetiology or a suspected sarcoidosis. All patients with normal thoracic tomography underwent an 18 F-FDG PET/CT, which was blindly reinterpreted. We then assessed the proportion of positive 18 F-FDG PET/CT and the impact on the final aetiology, using Abad's criteria for the diagnosis of intraocular sarcoidosis. Results: 19 of the 67 patients (28.4%) had mediastinal hypermetabolic foci on their 18 F-FDG PET/CT consistent with sarcoidosis. It identified a biopsy site in two cases, which were consistent with sarcoidosis. At the end of the study, six patients (10%) had a proven sarcoidosis, six patients (9%) were considered as having a presumed sarcoidosis and 18 patients (26.9%) as having indeterminate sarcoidosis. 18 F-FDG PET/CT enabled the diagnosis of presumed sarcoidosis in these six patients. An older age at diagnosis (p=0.004) and the presence of synechiae (p=0.02) were significantly related to an abnormal 18 F-FDG PET/CT, with a trend for an elevated ACE (p=0.0993). We established a nomogram to estimate the probability of having positive findings on the 18 F-FDG PET/CT according to different predictive factors. Conclusion: 18 F-FDG PET/CT enabled the diagnosis of intraocular sarcoidosis even in patients with a normal CT scan. Older age at diagnosis, presence of synechiae and elevated ACE are associated with positive findings on 18 F-FDG PET/CT consistent with sarcoidosis.